DESIGN OF RESIDENTIAL BUILDINGS TAKING INTO ACCOUNT THE CONSEQUENCES OF CLIMATE CHANGE IN UZBEKISTAN - Norov Nusratjon Nuralievich; Khudainazarova Yulduz Zhumanazarovna; Yakubov Shokhrukh; Saparboyev Dadakhon (Journals Park Publishing, 2022)
The article presents the factors influencing the consequences of climate change in the design of buildings in Uzbekistan.
Keywords: global climate change; weather; strategy